Pengaruh Kepemimpinan Kepala Sekolah terhadap Peningkatan Mutu Pembelajaran Melalui Kinerja Guru Sebagai Vaeiabel Intervening : Studi pada Guru SMA Negeri I Ketapang Kabupaten Sampang - Dirgantarawan Permana Putra; Chamariyah Chamariyah; Wasis Budiarto (Journal of Management and Creative Business, 2025)
The type of research is explanatory, the research approach used is quantitative, the research sample is 55 respondents. Data analysis using SPSS and PLS analysis. The objectives of this study are: 1) To test and analyze the direct influence of principal leadership on improving the quality of learning at SMA Negeri 1 Ketapang, Sampang Regency; 2) To test and analyze the direct influence of principal leadership on the performance of teachers at SMA Negeri 1 Ketapang, Sampang Regency; 3) To test and analyze the direct influence of teacher performance on improving the quality of learning at SMA Negeri 1 Ketapang, Sampang Regency; 4) To test and analyze the indirect influence of principal leadership on improving the quality of learning at SMA Negeri 1 Ketapang, Sampang Regency mediated by teacher performance. The results of the study indicate that: 1) Principal leadership has a significant effect on improving the quality of learning at SMA Negeri 1 Ketapang, Sampang Regency with an original sample value of 0.212; 2) Principal leadership has a significant effect on the performance of teachers at SMA Negeri 1 Ketapang, Sampang Regency with an original sample value of 0.411; 3) Teacher performance has a significant effect on improving the quality of learning at SMA Negeri 1 Ketapang, Sampang Regency with an original sample value of 0.528; 4) Principal leadership has a significant effect on improving the quality of learning at SMA Negeri 1 Ketapang, Sampang Regency mediated by teacher performance with an original sample value of 0.217 and a p-value of 0.030.